Communication and Environmental Politics in the Low Countries: Introduction to the Special Issue - Auge, Anais; van der Does, Ramon (Politics of the Low Countries, 2025)
Communication is central to environmental politics: from the speeches given at the United Nations Framework Convention on Climate Change (UNFCCC) plenary meetings and debates among members of parliament in environmental committees to the chanting of demands and grievances in climate protests and, say, everyday discussions about environmental problems among citizens. Through these varied forms of communication, people construct narratives about the environment that shape the way they understand problems, what solutions they think are available and, in the end, what they think should and should not be done (e.g. Louder & Wyborn, 2020). Environmental politics is thereby chiefly a discursive struggle in which people try to make others comply with their narrative about politics and the environment, prescribing its protagonists, heroes and villains, metaphors and plots (cf. Bamberg & Andrews, 2004; Crow & Jones, 2018; Stone, 2012).